Development of a scale to assess veterinary medicine students' attitudes toward biochemistry course - Fidan, Abdurrahman Fatih; Ocak, İjlal; Avcı, Gülcan; Denk, Barış (Afyon Kocatepe Üniversitesi)
Biochemistry stands as a pivotal subject in the curriculum of veterinary medicine education, warranting an assessment of veterinary students' attitudes towards this course. This study aims to develop a scale to gauge veterinary students' sentiments regarding biochemistry. The sample comprises 220 students enrolled in a veterinary medicine program. Initially, a preliminary test form with 49 items was created through a thorough review of relevant literature and expert consultation. A pre-test form was administered to 20 veterinary students to assess item clarity, grammar, and response duration, followed by necessary adjustments. Subsequently, the trial form was distributed to the 220 enrolled students. The data collected were analyzed, revealing a Kaiser-Meyer-Olkin (KMO) value of 0.794, indicating the adequacy of the scale. Exploratory factor analysis showcased factor loadings ranging from .582 to .812. Moreover, a reliability analysis demonstrated a Cronbach's Alpha coefficient of .761, surpassing the threshold of .70, signifying the scale's reliability. Thus, based on the findings, it can be concluded that the scale developed is both valid and reliable for assessing veterinary students' attitudes towards biochemistry.

Veteriner hekimlik eğitiminde, biyokimya temel bir ders olarak kabul edilir. Bu nedenle, veteriner hekimlik öğrencilerinin biyokimya dersine karşı davranışları ve duyarlılıkları, bu dersle ilgili tutumlarının ölçülmesini gerektirir. Bu araştırmanın amacı, veteriner hekimlik öğrencilerinin biyokimya dersine yönelik tutumunu ölçen bir ölçek geliştirmektir. Örneklemini, veteriner hekimlik fakültesinde eğitim gören 220 öğrenci oluşturdu. Araştırma kapsamında, öncelikle ilgili literatür tarandı, bir soru havuzu oluşturuldu ve 49 maddeden oluşan bir ön test formu uzman görüşü alınarak hazırlandı. Bu ön test formu, ölçek maddelerinin anlaşılabilirliği, dilbilgisi ve cevap süresi gibi faktörler açısından değerlendirilmek üzere 20 veteriner fakültesi öğrencisine uygulandı ve gerekli düzenlemeler yapılarak deneme formu veteriner fakültesindeki ve devam eden 220 öğrenciye uygulandı. Elde edilen veriler bilgisayar ortamına aktarılarak analiz edildi. Ölçeğin Kaiser-Meyer-Olkin (KMO) değeri .794 olarak belirlendi. Yapılan açıklayıcı faktör analizi sonucunda, ölçek maddelerinin faktör yüklerinin .582 ile .812 arasında değiştiği görüldü. Ayrıca, 16 maddeden ve 4 alt boyuttan oluşan bir ölçek elde edildi. Cronbach Alfa iç tutarlılık ve güvenirlik katsayısı .761 olarak bulundu. Bu değer, Cronbach Alfa katsayısı .70’in üzerinde olduğu için gelişitirilen ölçeğin güvenilir olduğunu göstermektedir.
Veteriner hekimliği öğrencilerinin biyokimya dersi konusundaki tutumlarını değerlendirmek için bir ölçeğin geliştirilmesi
Keywords: Attitude; Biochemistry; Scale Development; Veterinary Medicine; Biyokimya; Ölçek Geliştirme; Tutum; Veteriner Hekimliği